FOREIGN EXCHANGE-RISK PRICING IN THE NIGERIAN STOCK MARKET (2012)
Foreign Portfolio Investment (FPI) is a major source of liquidity to domestic firms. However, foreign exchange-risk makes returns to foreign investors uncertain thereby discouraging FPI. This uncertainty is more pronounced in developing economies where exchange rates play key roles and markets for hedging are underdeveloped. While studies from different economies have shown that firms hedge foreign exchange-risk or pay a premium to investors who bear it, previous studies on Nigeria have paid little attention to this important source of risk. A manifestation of this risk was the exchange rate depreciation from N117.97 per US dollars in 2007 to N132 in 2008 coinciding with an outflow of N633.96 billion from the Nigerian Stock Exchange (NSE). Therefore, this study analysed the foreign exchange-risk exposure and the premium (price) paid to risk-averse investors bearing this risk. The Adler and Dumas international capital asset pricing model was modified to incorporate the liquidity state of the NSE and this provided the framework for estimating the Fama and MacBeth two-pass regressions. Employing NSE data on 200 Nigerian firms from January 2000 to December 2009, the first-pass time-series regressions were used to estimate the risk exposure, while the second-pass pooled cross-sectional time-series regressions, with corrected standard errors, were used to estimate the risk prices. The pooled regressions solved the error-in-variable problem and the loss of the first five years typical of the Fama and MacBeth method. Deviations from Purchasing Power Parity (PPP) were also computed and used to complement changes in the bilateral rates and Real Effective Exchange Rate (REER) that were the conventional measures of foreign exchange-risk. Moreover, empirical analyses were broken down by firm-size, sector and episodes of exchange rate changes. More than 80.0% of Nigerian firms were exposed to bilateral exchange rate risk; over 60.0% to PPP-deviation risk and about 12.0% to REER risk. Foreign exchange-risk exposure was mostly negative; implying that Nigerian firms were net importers. Thus, because firms were unable to hedge their exposure to foreign exchange risk, their average monthly values reduced by 1.67% as a result of exchange rate depreciation. Foreign exchange-risk exposure was higher generally in larger firms and particularly in financial firms and there was the tendency for more firms to be exposed during episodes of naira depreciation. Further, foreign exchange-risk was priced (undiversifiable) on the NSE as risk-averse investors demanded a monthly premium of 1.65% on the bilateral rate risk, 0.99% on the PPP-deviation risk and 0.23% on the REER risk. Exposure to the bilateral exchange rate risk, the PPP-deviation risk and REER risk therefore raised the annual cost of capital of Nigerian firms by 19.80%, 11.88% and 2.76% respectively. The widespread foreign exchange-risk exposure commanded a risk premium on the Nigerian stock market. Therefore, the regulatory authorities should recognise that firms’ costs of capital tend to rise as Nigeria’s exchange rate system becomes more market-determined and should design appropriate instruments for hedging. Nigerian firms also need to actively manage their exposure to foreign exchange-risk.